"How Long Have I Got?"—A Prospective Cohort Study Comparing Validated Prognostic Factors for Use in Patients with Advanced Cancer. (12th April 2019) - Simmons, Claribel; McMillan, Donald C.; Tuck, Sharon; Graham, Cat; McKeown, Alistair; Bennett, Mike; O'Neill, Claire; Wilcock, Andrew; Usborne, Caroline; Fearon, Kenneth C.; Fallon, Marie; Laird, Barry J.; et al.
Abstract: Background: The optimal prognostic factors in patients with advanced cancer are not known, as a comparison of these is lacking. The aim of the present study was to determine the optimal prognostic factors by comparing validated factors. Materials and Methods: A multicenter, prospective observational cohort study recruited patients over 18 years with advanced cancer. The following were assessed: clinician‐predicted survival (CPS), Eastern Cooperative Oncology Group performance status (ECOG‐PS), patient reported outcome measures (anorexia, cognitive impairment, dyspnea, global health), metastatic disease, weight loss, modified Glasgow Prognostic Score (mGPS) based on C‐reactive protein and albumin, lactate dehydrogenase (LDH), and white (WCC), neutrophil (NC), and lymphocyte cell counts. Survival at 1 and 3 months was assessed using area under the receiver operating curve and logistic regression analysis. Results: Data were available on 478 patients, and the median survival was 4.27 (1.86–7.03) months. On univariate analysis, the following factors predicted death at 1 and 3 months: CPS, ECOG‐PS, mGPS, WCC, NC (all p < .001), dyspnea, global health (both p ≤ .001), cognitive impairment, anorexia, LDH (all p < .01), and weight loss ( p < .05). On multivariate analysis ECOG‐PS, mGPS, and NC were independent predictors of survival at 1 and 3 months (all p < .01). Conclusion: The simple combination of ECOG‐PS and mGPS is an important novel prognostic framework which can alert clinicians to patients with good performance status who are at increased risk of having a higher symptom burden and dying at 3 months. From the recent literature it is likely that this framework will also be useful in referral for early palliative care with 6–24 months survival. Implications for Practice: This large cohort study examined all validated prognostic factors in a head‐to‐head comparison and demonstrated the superior prognostic value of the Eastern Cooperative Oncology Group performance status (ECOG‐PS)/modified Glasgow Prognostic Score (mGPS) combination over other prognostic factors. This combination is simple, accurate, and also relates to quality of life. It may be useful in identifying patients who may benefit from early referral to palliative care. It is proposed ECOG‐PS/mGPS as the new prognostic domain in patients with advanced cancer. Abstract : This article examines prognostic factors in patients with advanced cancer, comparing validated factors to determine which are optimal.